تطبيق المواد البلورية السائلة في كروماتوغرافيا الغاز- السائل - وادي, أمل ناجي; عبدالله, زينب، محمود; دحام, هادي كريم; دحام, هادي كريم (Al-Nahrain Journal of Science, 2013)
The objective goal of this research was concentrated on synthesize liquid crystalline which identified using FT-IR and the thermal crystalline characteristic were also investigated using the DSC and hot-stage polarized microscope technigues, the liquid crystalline, which showed great thermal stability over wide range of temperatures, has proposed to be applied as a stationary phase in gas liquid chromatography, some organic compounds which similar in atomic carbon number but different in geometrical stricture were sucessfully analyzed on the chromatography columns.